Eurasian clinical guidelines for the prevention of cardiovascular diseases in childhood and adolescence (2023) - O. A. Kislyak; I. V. Leontyeva; A. V. Starodubova; A. A. Alersandrov; M. G. Bubnova; Yu. R. Varaeva; A. A. Kamalova; L. V. Kozlova; E. V. Pavlovskaya; D. A. Polunina; V. A. Revyakina; V. B. Rozanov; et al. (Евразийский Кардиологический Журнал, 2023)
The EAC Guidelines represent the views  of the  EAC,  and were produced  after careful consideration  of the scientific  and medical knowledge,  and the evidence  available at the time of their publication.